Studi Eksperimental Beton Mutu Normal Dengan Agregat Batok Kelapa Dan Terak Nikel - Putri Aprilia; Frans Phengkarsa; Benny Kusuma (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
This study aims to determine the value of compressive strength, split tensile strength, flexural strength, and modulus of elasticity in normal quality concrete with variations of coconut shell and nickel slag added materials in coarse aggregate. Making test objects in the form of cylinders 150 mm x 150 mm x 300 as many as 27 pieces and beams 150 mm x 150 mm x 600 mm as many as 9 pieces. The results showed that the addition of coconut shells and nickel slag to coarse aggregate for testing concrete with a mixture of 30% nickel slag and 20% coconut shells obtained values for the 28th day of compressive strength, namely 30,841MPa, 31,124MPa and 31,690MPa, strong Split tensile strength is 3,114MPa, 3,468MPa and 3,255MPa, respectively, the flexural strength values are 4,383MPa, 4,018MPa and 3,930MPa, respectively. And for the modulus of elasticity, the values obtained are 12763,274MPa, 15404,333MPa, and 13619,275MPa.